Management in a time of radical uncertainty - Jacquinet, Marc (2021)
Societies are still, now, indubitably, in the middle of a major sanitary and health crisis, all over. If April 2020 was a time of local lockdown in Asia, Europe and the Americas, it is expanding globally, and countries that are unable or unwilling to manage the spread of the disease are putting their health system as well as their social and economic activities under pressure, without ignoring the heavy toll on human populations. The impact of the Sars-CoV-2 and the resulting disease for humans is already tremendous, above 3 percent of GDP for the first quarter of 2020 and above 15 or 20 percent for the whole current year. According to the World Trade Organization (WTO 2020) the decline of global trade is reckoned between 13 and 32 % (OECD 2020).